O dwudziestowiecznych związkach retoryki z dydaktyką stylistyki = The 20th century relations between rhetoric and didactics of stylistics - Bogołębska, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The 20th century relations between rhetoric and didactics of stylistics were richly manifested in school poetics of the normative character being one of the sources of knowledge about didactics of stylistics which were published until the outbreak of II World War.
Keywords: retoryka; dydaktyka stylistyki; 20 w.